Do no harm - McDonald, Christina (Gallery Books, 2021)
Mother of a kindergartener, married to her police detective soulmate, Emma has a rewarding career as a doctor at the local hospital. When her son, Josh, is diagnosed with a rare form of cancer, she is determined to save him. Emma makes the risky decision to sell opioids to fund the life-saving treatment Josh needs. When somebody ends up dead, a lethal game of cat and mouse ensues-- with her own husband leading the chase. With her son's life hanging in the balance, Emma is dragged into the dark world of drugs, lies, and murder. -- adapted from back cover